TRADISI NGEBOM DI KECAMATAN PENDOPO KABUPATEN EMPAT LAWANG DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Apri, Rudi; Harun, Muhammad; Tamuddin, Muhammad (Muamalah, 2020)
ABSTRACT Human life is required to interconnect and interweave ropes among others, this is called the term Hablum minnnas. Through the relationship will be a sense of solidarity, kinship, and help each other, one of which is to help in the form of accounts receivable debt. Through debt is the receivables that human beings can each other lighten each other's burden. It is right to say that this aspect of debt is very important in terms of relieving baban for people in need, because the debt of accounts can give happiness, and also can be one of the good deeds in Islam. The object of research in this thesis is the debt of materials groceries in the form of tradition, as for the problems that become the main target of the author in this thesis is how the debt mechanism of groceries groceries in the form of this tradition. While the type of research used is the type of field research where the data source obtained and collected from the results of data processing in the field are closely related to the title of this thesis. Types of sources and data in this study in the form of qualitative data is the data in the form of a description of something related from the primary data and secondary data collection techniques of this data by way of interviews, and documentation associated with this thesis. So it can be concluded that the implementation of the mechanism of debt in the form of materials receivables sembako in Pendopo District Empat Lawang based on this tradition is very useful for the community involved. This is clearly permitted or prohibited by Islamic law. Whereas in the transaction of debtors' receivables of materials grown in the Pendopo Sub-district of Empat Lawang Regency there must be a willingness between both parties as a lender and the party who is given the debt. Keywords: Tradition, Ngebom, debt Kehidupan manusia dituntut untuk saling berhubungan dan menjalin tali silaturahmi antar sesama, ini yang disebut dengan istilah Hablum minnnas. Melalui hubungan tersebut akan terjalin rasa solidaritas, kekeluargaan, dan tolong menolong antar sesama, salah satu diantaranya ialah tolong menolong dalam bentuk utang piutang. Adapun objek penelitian ini ialah utang piutang bahan sembako dalam bentuk tradisi. bagaimanakah mekanisme utang piutang bahan sembako dalam bentuk tradisi ini. Sedangkan jenis penelitian yang digunakan adalah jenis penelitian lapangan dimana sumber datanya diperoleh dan dikumpulkan dari hasil pengolahan data di lapangan yang erat kaitannya dengan judul skripsi ini. Penelitian ini berupa data kualitatif.teknik pengumpulan data ini dengan cara wawancara, dan dokumentasi yang berhubungan dengan masalah yang diteliti. Hasil penelitian bahwa pelaksanaan mekanisme utang piutang dalam bentuk bahan sembako di Kecamatan Pendopo Kabupaten Empat Lawang yang berbasis tradisi ini diperbolehkan oleh syariat Islam dengan syarat: harus ada kerelaan di antara kedua belah pihak baik sebagai pemberi utang maupun pihak yang diberi utang. Kata kunci: Tradisi, Ngebom, Utang-piutang